Various therapies in the treatment of patients with medial compartment osteoarthritis of knee joint: A review of literature - Behnam Soleymani; Mostafa Kamali; Ali Tahmasebi; Tahmoureth Tahmasebi (Vesnu Publications, 2015)
Introduction: knee joint osteoarthritis is one of the most prevalent musculoskeletal problems in adult population, which cause pain and functional limitations. Involvement of medial compartment is almost 10 times more common than lateral compartment, which results in varus deformity among patients with medial compartment osteoarthritis of knee joint. Main objectives in the treatment of knee joint osteoarthritis are reducing pain, improving physical functions and reducing the progress of the disease. Treatments of knee joint osteoarthritis are classified in two categories: operative treatment and conservative treatment. The aim of this study is to investigate the effect of different therapies in the treatment of patients with medial compartment osteoarthritis of knee joint. Methods & Materials: An extensive electronic search was carried out through internationally published scholarly articles in ScienceDirect, Pubmed and Google Scholar from 1973 to 2014. Methodological quality of papers was assessed using Down and Black checklist. Results: With the literature search, we identified 60 papers. 24 articles were acquired in full text on the basis of inclusion criteria for further evaluation. The scores of reporting, external validity, internal validity (bias) and internal validity (confounding) were 2 to 9, 1 to 3, 2 to 5 and 2 to 5 respectively. Conclusion:   Among different non-surgical therapies in the treatment of patients with medial compartment osteoarthritis of knee joint, all therapies had reported satisfactory results in reducing pain and disability, but with regard to low number of available literature, more randomized clinical trials are needed so that one can achieve determinable results in this regard. Keywords: Knee joint osteoarthritis, Physiotherapy, Weight loss, knee brace, Lateral wedge insole